Adoption of clarified international standard of auditing (ISAs) and international standard of quality control (ISQC) in small and medium practice (SMP) in Malaysia / Ang Soon Yong - Ang, Soon Yong (2013)
Recently, adoption of the Clarified International Standard of Auditing (Clarified ISAs) and International Standard of Quality Control (ISQC) have gain steady attention from various accounting practitioners and academicians. This Clarity project began in 2004 and was completed in February 2009. After 2 years of adoption of Clarified ISAs and ISQC, it is time for the practitioners to provide the feedback to the International Auditing and Assurance Standard Board (IAASB) on post implementation review of Clarified ISAs and ISQC. The study seeks to survey the internal resource preparedness of the Small and Medium Practice (SMP) for adoption of Clarified ISAs and ISQC by applying resource-based view theory. Further, impact of Clarified ISAs and ISQC on timeliness on audit report had been investigated. Standard multiple regression was used to analyse data from 115 respondents from Small and Medium Practice (SMP) in Malaysia. Based on the result of analysis, the study evidenced that the organizational resources and intellectual resources preparedness lead to the adoption of Clarified ISAs and ISQC among SMP in Malaysia. Besides, the adoption of Clarified ISAs and ISQC also affects the timeliness of audit report. Nevertheless, there are no significant association found between financial resource preparedness, human resource preparedness and the adoption of clarified ISAs and ISQC. Findings from the study have implications for academicians, regulatory bodies, auditing standard setters, professional accounting bodies, audit firms and auditees toward the adoption of Clarified ISAs and ISQC.